Broadband, Spectrally Conrolled raman-active Attenuator - Holtmannspötter, Michael; Pitschujew, E.; Schmauß, Bernhard (The European Conference on Optical Communication 2009 (ECOC 2009), Wien, September, 2009)
We present numerical investigations on a broadband Raman-active attenuator using a WDM-scheme of control signals. It is shown to hold a feasible control characteristic for mitigation of residual transients arising in spite of inline-amplifier control.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.broadb